Developing a professional-practice-model-based nursing organizational informatics competency model. (October 2022) - Chen, Yuan; Cai, Zhenzhen; Lin, Bixia; Yan, Lijuan; Zheng, Weiliang; Kuo, Ming-Chuan; Hübner, Ursula; Chang, Polun
Highlights: Established a scientific nursing organizational informatics competency model. Nursing organizational informatics competency model is crucial for the healthcare organization. Providing an action plan to develop organizational nursing informatics competencies. Abstract: Background: The development of nursing informatics started late in China. There is an urgent need to develop a clinical practice model that can guide nursing managers in constructing an organizational nursing informatics competency. Objective: The objective of this study was to develop a nursing organizational informatics competency model based on the Professional Practice Model (PPM) and to provide a reference for training in clinical nursing informatics in hospitals. Methods: A multidisciplinary team in the hospital was first formed as the working group, consisting of nurses trained with the TIGER (Technology Informatics Guiding Education Reform) Taiwan model and had practical experience in system development. We used an exploration map to help build the prototype of the hospital nursing informatics competency model. Then, a final model was constructed by experienced out-of-hospital experts using the Delphi method. The final model was determined according to the validity analysis. Results: Ten hospital stakeholders were invited to form the multidisciplinary working team to develop the prototype organizational PPM model. Two rounds of Delphi were conducted to twelve experienced nurses' informatics experts outside the hospital by e-mail. The results showed that the questionnaire return rate was 100 %, the expert authority coefficient was 0.84, the general validity of the two rounds of content was 92.46 % and 100 %, respectively, and the coefficient of variation of all items was < 0.3. The final model included five categories, including management strategy and leadership, organizational structure and operation, improvement of the environment for nursing information practice, cultivation of core competence in nursing information, and project management of the nursing information system, with 61 elements in total. Conclusions: We propose this model to help hospital nursing managers to establish a plan of action to build up organizational clinical informatics competency.